PENINGKATAN LITERASI KEUANGAN MELALUI EDUKASI MENABUNG SEJAK DINI PADA ANAK-ANAK RUMAH PENYULUHAN KREATIF JAKARTA SELATAN - Muhammad Abdul Muis; Suwardi Suwardi; Agus Amri Mokoginta; Yudhi Yuliansyah; Alpaizon Yasa Putra; Aldilla Saeba (Jurnal Pengabdian Bukit Pengharapan, 2026)
Financial literacy is a fundamental competency that should be introduced from an early age to foster responsible and sustainable financial behavior. However, many children still have limited understanding of basic financial management, particularly regarding the importance of saving. This condition presents a challenge in developing future generations who are capable of making sound financial decisions and planning for their future needs. This community service activity aimed to improve children's financial literacy through early-age saving education at Rumah Penyuluhan Kreatif, South Jakarta. The program was conducted on August 31, 2025, involving 25 participants aged 7–10 years. The methods employed included educational presentations on the importance of saving, interactive discussions, educational games, and practical activities in which participants wrote their future aspirations on piggy banks as motivation to save. The results indicated that participants gained a better understanding of the benefits of saving, the importance of setting aside money for future needs, and demonstrated high enthusiasm throughout the activities. In addition to improving participants’ knowledge of basic financial management, the program also contributed to the development of discipline, responsibility, and future-oriented thinking. Therefore, saving education delivered through interactive and engaging approaches can serve as an effective strategy for enhancing children's financial literacy and promoting healthy financial behavior from an early age.